Review of Uta G. Poiger. 2000. Jazz, Rock, and Rebels: Cold War Politics and American Culture in a Divided Germany. Berkeley: University of California Press - Jackson, Jeffrey H. (Current Musicology, 2001)
Over the last several years, cultural historians have looked to jazz music as a way of talking about national identity. For historians of the United States, the logic is easy to understand. Jazz is, unquestionably, an integral part of the American story. But more importantly, as historians continue to rework the narrative of U.S. history to incorporate the issue of race more completely, jazz must be discussed as a crucial point of connection between whites and blacks in this country. To exclude jazz-not just as a musical form, but as a cultural phenomenon-would be historically inaccurate, and it would give a skewed view of how American national identity has evolved in the twentieth century. Understanding how jazz fits into definitions of European national identity, however, is a bit trickier. In the U.S., the early popularity of jazz challenged views of America as a country with distinctly “white” and “black” or “high” and “low” cultures that rarely ever met, and the music quickly came to be seen as an essential part of American life (Leonard 1962; Levine 1993). In Europe, however, the consequences of jazz’s popularity were more complicated for critics and cultural commentators-for Europeans, jazz was a “foreign” music. Therefore, it not only evoked conflicts about race and the boundaries between “high” and “low” culture (which were already subject to debate by the 1920s), it also raised questions about “Americanization” and the invasion of foreigners at a time when discussions of national identity had been energized by war and propaganda that saw “others” as enemies. Jazz quickly became a part of the “culture wars” of many countries in the 1920s and 1930s as they tried to renegotiate their sense of nationhood. At that moment, war, Depression, changes in international diplomacy, immigration, and the expansion of a global economy where goods and ideas easily crossed borders, all called older definitions of the nation into question. Jazz did not help to make things clearer. As in the U.S., the early debates about jazz in Europe were rarely only about the music itself. Rather, they doubled as complex attempts to reimagine national identity.